REPRESENTATION OF INDONESIAN CULTURE IN “ONLY IN INDONESIA” VIDEO BY LASTDAY PRODUCTION - Andre Ikhsano; Yolanda Stellarosa; Lusiana Cindy Irawan; Mengmeng Guo (ASPIRATION Journal, 2021)
Culture can be formed from habits acquired by humans as members of society. Indonesia has so many ethnic groups and produces different habits. From the habits carried out by the community; it is not uncommon to have bad habits and unique habits. This is what makes one of the videos with a cultural theme that is considered satire through one of the social media platforms, which is Youtube, entitled "Only in Indonesia" by LASTDAY Production, interesting to study. Using a descriptive qualitative methodology with Roland Barthes' semiotic analysis which focuses on the meaning of denotation, connotation, and myth; this study aims to determine the representation of Indonesian culture through the scenes in the Youtube video. The results show that there are five of the seven elements of universal culture, namely, social organization systems, technology and equipment systems, knowledge systems, arts, and religion. In addition, the representation of Indonesian culture contained in the video "Only in Indonesia" is a culture that can be said to be negative, seen from the depiction of people's habits. Keyword: Representation, Indonesia Culture, Youtube Video, Semiotics